Herpes simplex virus type 2 (HSV-2) genital shedding in HSV-2-/HIV-1-co-infected women receiving effective combination antiretroviral therapy. (March 2016) - Péré, Héléne; Rascanu, Aida; LeGoff, Jérome; Matta, Mathieu; Bois, Frédéric; Lortholary, Olivier; Leroy, Valériane; Launay, Odile; Bélec, Laurent; ,
The dynamics of genital shedding of HSV-2 DNA was assessed in HIV-1-infected women taking combination antiretroviral therapy (cART). HIV-1 RNA, HIV-1 DNA and HSV DNA loads were measured during 12–18 months using frozen plasma, PBMC and cervicovaginal lavage samples from 22 HIV-1-infected women, including 17 women naive for antiretroviral therapy initiating cART and 5 women with virological failure switching to a new regimen. Nineteen (86%) women were HSV-2-seropositive. Among HSV-2-/HIV-1-co-infected women, HIV-1 RNA loads showed a rapid fall from baseline after one month of cART, in parallel in paired plasma and cervicovaginal secretions. In contrast, HIV-1 DNA loads did not show significant variations from baseline up to 18 months of treatment in both systemic and genital compartments. HSV DNA was detected at least once in 12 (63%) of 19 women during follow up: HSV-2 shedding in the genital compartment was observed in 11% of cervicovaginal samples at baseline and in 16% after initiating or switching cART. Cervicovaginal HIV-1 RNA loads were strongly associated with plasma HIV-1 RNA loads over time, but not with cervicovaginal HSV DNA loads. Reactivation of genital HSV-2 replication frequently occurred despite effective cART in HSV-2-/HIV-1-co-infected women. Genital HSV-2 replication under cART does not influence cervicovaginal HIV-1 RNA or DNA shedding.